The Effect of Firm Size and FDR on ROA Through BOPO as an Intervening Variable at Islamic People's Economic Banks (BPRS) in Indonesia - Ridho Muarief; Setiyawan, Agustinus Doedyk; Priyanto, Priyanto; Setyawan, Dimas Ari (Indonesian Journal of Banking and Financial Technology, 2024)
This study compares the effects of financing to deposit ratio (FDR) and bank size (firm size) on return on equity through BOPO as an Intervening Variable at Islamic People's Economic Bank (BPRS) in Indonesia. The data collection method is done through indirect observation method in the form of secondary data from Sharia People's Economic Bank monthly financial statements (BPRS). Using a purposive sampling technique, 60 BPRS data were included in the sample. Data analysis using Eviews version 9 tool involved path analysis. While FDR, BOPO, and Size had a significant negative impact on profitability, the T test results indicated that it had a significant positive impact but had no significant negative effect on profitability, while NPF was able to mediate FDR, BOPO, and SIZE on profitability, while NPF was unable to mitigate the impact on earnings.